Publicity media use, ecological policy cognition and farmers’ green production behaviors: evidence from Hainan, China - Qiao, Dan; Zhu, Yuanxiang; Ren, Qiongyao; Xu, Tao; Xu, Shuting (Frontiers in Sustainable Food Systems, 2025)
Farmers’ green production behaviors are of great significance in promoting the green development of agriculture and enhancing the level of rural ecological civilization construction. Based on the research data from four cities and counties in Hainan Province, this study explored the role mechanisms between publicity media use, ecological policy cognition and farmers’ green production behaviors using Ordered Logit model and Mediated effect model, addresses the underexplored differential impacts of traditional publicity media use and new publicity media use on farmers’ green production behaviors. The results show that (1) publicity media use and ecological policy cognition have a significant positive effect on farmers’ green production behaviors, (2) ecological policy cognition plays a mediating role in publicity media use on farmers’ green production behaviors, (3) there is a difference in the effect of different types of publicity media use on farmers’ green production behaviors, with new publicity media use having a stronger direct effect, while the traditional publicity media influence is more mediated by ecological policy cognition. Based on these findings, the government should improve the level of rural information infrastructure, emphasize the role of media in improving farmers’ ecological policy cognition, and strengthen the training of new publicity media use.